Dampak pemberian daun mangrove avicennia marina (api-api putih) terhadap pertumbuhan teripang pasir (Holothuria scabra) di perairan Hansisi Kabupaten Kupang - Londong, Daud; Dahoklory, Nicodemus; Sunadji, Sunadji (Jurnal Aquatik, 2023)
. Sand sea cucumbers are known as a basic ingredient for medicines because of their protein content. This can trigger the exploitation of sand sea cucumbers, which will impact fishermen's income. This research aims to determine the effect of giving mangrove leaves and to determine the correct dose on the growth of sand sea cucumbers (Holothuria Scabra). The design of this study used a Completely Randomized Design (CRD), where the treatment given was A. marina (Api-api Putih) mangrove leaves fermented with EM4 at different doses, namely 4 treatments with 3 replications. Treatment A: Feeding Avicennia marina (White api-api) mangrove leaves at a dose of 310 grams/container, Treatment B: Feeding A. marina (White api-api) mangrove leaves at a dose of 320 grams/container, Treatment C: Feeding mangrove leaves A. marina (White fire) dose of 330 grams/container, and Treatment D: Feeding mangrove leaves A. marina (White fire) dose of 340 grams/container. The research results showed that the highest growth was in treatment C with a value of 72 grams, followed by treatment B with a value of 31.66 grams, treatment A 16.66 grams, and treatment D with a value of 6.66 grams as the lowest growth. The results of the anova analysis showed P>0.05% and 0.01%, meaning that the treatment had a real effect. The BNT test results showed that there was a difference between treatment C and treatments A, B and D. Thus, treatment C had optimal weight growth. The results of the average survival percentage of sand sea cucumbers obtained showed that treatments A, B, C and D had similar value results, amounting to 100%. The results of the water quality parameters were obtained, the temperature range was 27-280C, salinity 29-32 ppt, and pH between 7.6-8.0.